2016
DOI: 10.1177/1465116516657672
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual communication for whom? Language policy and fairness in the European Union

Abstract: This article compares the effectiveness and the fairness of four alternative policies aimed at managing multilingual communication in the European Union. The current multilingual regime, based on the formal equality among the official languages of the European Union Member States disenfranchises only a small percentage of residents. On the contrary, an English-only language policy would exclude 45% to 79% of adult residents in the 25 countries for which data are available, depending on the indicator used. A la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(36 citation statements)
references
References 32 publications
0
35
0
1
Order By: Relevance
“…However, research (e.g. Ammon, 2006Ammon, , 2012Author 2006;2015;Cogo & Jenkins, 2010;Gazzola, 2006Gazzola, , 2016Koskinen, 2013;Lenaerts, 2001;Piron, 1980;Quell, 1997;van Els, 2005;Wright, 2009) and internal inspections (e.g. JIU/REP/2011/4, see below) within these organisations have long shown that reductions in multilingual provision and use are commonplace, and multilingual language policies have been difficult to implement.…”
Section: Lpp and Supra-national/international Organisationsmentioning
confidence: 99%
“…However, research (e.g. Ammon, 2006Ammon, , 2012Author 2006;2015;Cogo & Jenkins, 2010;Gazzola, 2006Gazzola, , 2016Koskinen, 2013;Lenaerts, 2001;Piron, 1980;Quell, 1997;van Els, 2005;Wright, 2009) and internal inspections (e.g. JIU/REP/2011/4, see below) within these organisations have long shown that reductions in multilingual provision and use are commonplace, and multilingual language policies have been difficult to implement.…”
Section: Lpp and Supra-national/international Organisationsmentioning
confidence: 99%
“…And, secondly, the more we reject an elitist and top‐down understanding of partisanship and reconceive partisanship as a bottom‐up inclusive and deliberative process, the more problematic it is to ignore the deep linguistic diversity that exists among ordinary EU citizens. Indeed, recent empirical research has shown that abandoning the current regime of full official multilingualism in the EU and adopting either an English‐only or an English‐French‐German language regime would disenfranchise up to 79 per cent and up to 49 per cent of adult residents in the EU, respectively (Gazzola, ). This suggests that transnational EU parties using a bottom‐up deliberative model could not resort to the use of a lingua franca without undermining their inclusiveness and remaining elitist.…”
Section: Multilingualism and The Linkage Function Of Parties: Agaimentioning
confidence: 99%
“…Furthermore, scholars in the linguistic justice tradition examine linguistic heterogeneity and the implications of language inclusion—or exclusion—within institutions on the policymaking process (e.g. Gazzola, 2016b; Liu and Baird, 2012). How does the choice of a lingua franca in a multilingual society affect a court and its judges?…”
Section: Introductionmentioning
confidence: 99%